A role for below‐ground biota in plant–plant facilitation. (9th October 2013) - Rodríguez‐Echeverría, Susana; Armas, Cristina; Pistón, Nuria; Hortal, Sara; Pugnaire, Francisco I.
Summary: Plant–plant facilitation is an important driver of plant diversity, which in turn maintains ecosystem multifunctionality and can buffer some negative effects of climate change. Facilitation is classically attributed to the amelioration of environmental extremes and resource availability. Integrating below‐ground biota into the positive plant interactions framework should provide a more realistic understanding of this process, enabling us to gain insights into the dynamics of below–above‐ground communities. We tested the effect of below‐ground biota on the performance of a plant community and of individual species using soil extracts from the understorey of a benefactor plant species and adjacent open spaces. Soil bacteria from extracts and experimental microcosms were analysed using pyrosequencing. Soil biota had a significant effect on the abundance, growth, functional traits and reproductive output of beneficiary plant species through processes that are independent of the direct influence of the benefactor species. Different soil bacterial communities were associated with the benefactor species, the individual beneficiary plant species and the plant community, revealing complex below–above‐ground links between plants and soil microbiota. Synthesis . The below‐ground biota cultivated by benefactor plant species play a fundamental role in positive interactions between plant species contributing to the preservation of diversity and the evolution of plant communities. Abstract : Below‐ground biota cultivated by nurse plant species increase plant number and biomass in plant communities and lead to a better performance of single plant species. In turn, plant identity and growth determine soil bacterial communities composition. Soil microbiota play a fundamental role in positive interactions among plants contributing to the preservation of diversity and the evolution of plant communities